Shariah Penal Code Order, 2013 of Negara Brunei Darussalam: Its Implementation and Challenges - Abdul Mohaimin bin Noordin Ayus (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Shariah, or Islam law, is not foreign to Negara Brunei Darussalam. Its implementation started since the conversion of Awang Alak Betatar to the Islamic faith and assumed the royal name of Sultan Muhammad Shah (1363-1402 M).[1] Brunei, then, had officially accepted Islam as the religion of the ruler and the ruled; and thenceforth the birth of a new nation known as “Negeri Brunei”, a Malay Islamic Monarchy state (Kerajaan Kesultanan Melayu Islam.[2] The monarchy system was officially established since early 15th century with the conversion of Awang Alak Betatar and this Islamic Monarchy State has remained till today. * Prof. Dr. Haji Abdul Mohaimin Ayus bin Haji Noordin Ayus, Former Dean, Faculty of Shariah and Law, Universiti Islam Sultan Sharif Ali (UNISSA), Negara Brunei Darussalam. Any opinions expressed in this paper is the writer’s own personal view which shall not represent the view and policy of UNISSA or any government agencies of Negara Brunei Darussalam, except those which have been duly acknowledged by citations referred to in the footnotes. This paper is a concise translation of the original paper “Perintah Kanun Hukuman Jenayah Syariah, 2013 Brunei Darussalam: Pelaksanaan dan Cabaran” which was earlier submitted. [1] See Abdul Mohaimin Ayus. “Memperkasakan Undang-undang Jenayah Syarak: Analisis Perundangan Perbandingan Antara Brunei dan Malaysia”. Prosiding Seminar Isu-Isu Kontemporari Dalam Syariah dan Undang-Undang, organized by the Faculty of Shariah and Law, Universiti Islam Sultan Sharif Ali (UNISSA), Negara Brunei Darussalam. 1432H/2011M, pp. 76-108. See also Prof. Dato’ Dr. Haji Mahmud Saedon bin Awang Othman. (1996). Perlaksanaan dan Pentadbiran Undang-undang Islam di Negara Brunei Darussalam: Satu Tinjauan. Bandar Seri Begawan: Dewan Bahasa dan Pustaka Brunei, p. vii. [2]Ibid., p. 19. Pengiran Dato Seri Setia Dr. Haji Muhammad bin Pengiran Haji Abd. Rahman. (2007). Islam di Brunei Darussalam Zaman British (1774-1984). Bandar Seri Begawan: Dewan Bahasa dan Pustaka Brunei, hal. 68-93. Pengiran Dato Seri Setia Dr. Haji Muhammad, at p. 92: “Berdasarkan sumber China dan sumber tradisi, Awang Alak Bertatar dipercayai menganut Islam pada atau sebelum 1371. Oleh itu kunjungan baginda ke Melaka pada awal abad ke-15 itu adalah dalam sifat baginda seorang raja atau sultan yang sudah menganut Islam sejak lebih tiga puluh tahun sebelumnya.” (Based on Chinese and traditional sources, Awang Alak Bertatar was believed to have embraced Islam in or before 1371. His visit to Malacca in the early 15thcentury was in the capacity of a king or sultan who had embraced Islam for more than thirty years before.)